Targeted array CGH as a valuable molecular diagnostic approach: Experience in the diagnosis of mitochondrial and metabolic disorders - Wang, Jing; Zhan, Hongli; Li, Fang-Yuan; Pursley, Amber N.; Schmitt, Eric S.; Wong, Lee-Jun (Molecular genetics and metabolism, 2012)
Oligonucleotide array-based comparative genomic hybridization (aCGH) targeted to coding exons of genes of interest has been proven to be a valuable diagnostic tool to complement with Sanger sequencing for the detection of large deletions/duplications. We have developed a custom designed oligonucleotide aCGH platform for this purpose. This array platform provides tiled coverage of the entire mitochondrial genome and high-density coverage of a set of nuclear genes involving mitochondrial and metabolic disorders and can be used to evaluate large deletions in targeted genes. A total of 1280 DNA samples from patients suspected of having mitochondrial or metabolic disorders were evaluated using this targeted aCGH. We detected 40 (3%) pathogenic large deletions in unrelated individuals, including 6 in genes responsible for mitochondrial DNA (mtDNA) depletion syndromes, 23 in urea cycle genes, 11 in metabolic and related genes. Deletion breakpoints have been confirmed in 31 cases by PCR and sequencing. The possible deletion mechanism has been discussed. These results illustrate the successful utilization of targeted aCGH to detect large deletions in nuclear and mitochondrial genomes. This technology is particularly useful as a complementary diagnostic test in the context of a recessive disease when only one mutant allele is found by sequencing. For female carriers of X-linked disorders, if sequencing analysis does not detect point mutations, targeted aCGH should be considered for the detection of large heterozygous deletions. ► Detect large deletions in nuclear and mitochondrial genomes by targeted aCGH. ► Precisely map the mtDNA large deletion breakpoints and estimate the mtDNA content. ► Discussed the possible deletion mechanism based on deletion breakpoint mapping. ► Targeted aCGH is useful in diagnosis of mitochondrial and metabolic disorders.